Adaptive collaborative approaches in natural resource governance : rethinking participation, learning and innovation - Ojha, Hemant R. (Earthscan studies in natural resource management., 2012)
The purpose of this book is to showcase a range of approaches that consider learning and collaboration as central processes in agriculture and natural resources governance and management. These include four related and overlapping adaptive collaborative approaches - Adaptive Collaborative Management, Participatory Action Research, Social Learning and Innovation Systems. Despite these being generated in different institutional domains with somewhat diverse epistemological and policy orientations, the authors show that there are common themes among these approaches. The book presents.